2006
DOI: 10.2174/156652306777592027
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon Vectors as Outstanding Tools to Study and Modify Cognitive Functions

Abstract: This review summarizes recent data on the use of HSV-1-based amplicon vectors for in vivo gene delivery to the brains of rats and mice to study and modify behaviour. Here we describe studies that have focused on cognitive functions like learning and memory. In addition, the use of amplicons in other behavioural studies, like addiction, social interaction, anxiety and stress, will be briefly updated. Several remarkable findings have been achieved, thanks to the use of these very efficient and non-toxic naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Microarray analysis provides both the tools and the groundwork for the development of hypothesis-driven functional validation studies to confirm the roles of potential molecular pathways identified with genomic technology. To determine how these genes and pathways are co-regulated will require future research using various molecular biology and genetic approaches such as the use of transgenic technology (Havekes and Abel, 2009) and viral and non-viral gene targeting (Burger et al, 2005; Jerusalinsky and Epstein, 2006; Lundberg et al, 2008; Schubert et al, 2008; Southgate et al, 2008). …”
Section: Sub-regional Differences In Gene Expression Correlate With Cmentioning
confidence: 99%
“…Microarray analysis provides both the tools and the groundwork for the development of hypothesis-driven functional validation studies to confirm the roles of potential molecular pathways identified with genomic technology. To determine how these genes and pathways are co-regulated will require future research using various molecular biology and genetic approaches such as the use of transgenic technology (Havekes and Abel, 2009) and viral and non-viral gene targeting (Burger et al, 2005; Jerusalinsky and Epstein, 2006; Lundberg et al, 2008; Schubert et al, 2008; Southgate et al, 2008). …”
Section: Sub-regional Differences In Gene Expression Correlate With Cmentioning
confidence: 99%
“…A large number of in vitro and in vivo studies using helper-free amplicons that cannot be described in this short review, have shown the outstanding potential of these vectors for gene therapy of neurological diseases, 26 Herpes simplex virus type 1-based vectors AL Epstein for the treatment of brain and other malignancies, 27 for fundamental studies of neurobiological 28 or virological 29 interest, and as genetic vector vaccines against pathogens. 30 Despite encouraging results, translation to large animal models is challenging and concern remains about clinical application, except perhaps for cancer treatment.…”
Section: Prospectsmentioning
confidence: 99%
“…Based on the affinity of HSV‐1 to the neuron and the appearance of improved HSV‐based constructs, like amplicons (Jerusalinsky & Epstein , 2 006), this will still be a viral of choice in gene therapy for chronic pain. In order to use HSV‐1‐based gene therapy to target the endogenous pain modulatory system, it is important (1) to distinguish neurons involved in nociceptive processing from neurons participating in other brain functions, and (2) to ascertain how HSV‐1 constructs will migrate retrogradely upon local delivery.…”
Section: Gene Therapy: An Eclectic Way To Manipulate the Supraspinal mentioning
confidence: 99%